2013
DOI: 10.1101/lm.029975.112
|View full text |Cite
|
Sign up to set email alerts
|

The role of contingency awareness in single-cue human eyeblink conditioning

Abstract: Single-cue delay eyeblink conditioning is presented as a prototypical example of automatic, nonsymbolic learning that is carried out by subcortical circuits. However, it has been difficult to assess the role of cognition in single-cue conditioning because participants become aware of the simple stimulus contingency so quickly. In this experiment (n ¼ 166), we masked the contingency to reduce awareness. We observed a strong relationship between contingency awareness and conditioned responding, with both trace a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 29 publications
(42 reference statements)
1
15
0
1
Order By: Relevance
“…Thus, differential conditioning, which is more difficult than single-cue conditioning, may be more dependent on awareness (LaBar & Disterhoft, 1998). However, using a false pretense masking task, involving reporting letter cues at a similar volume as CS volume, awareness was found to be critical for acquisition of both delay and trace single-cue eyeblink conditioning (Weidemann, Best, Lee, & Lovibond, 2013). Therefore, while trace conditioning appears to critically depend on awareness, data regarding the role of awareness in delay conditioning appears more equivocal.…”
Section: Declarative Memory and Trace Conditioningmentioning
confidence: 99%
“…Thus, differential conditioning, which is more difficult than single-cue conditioning, may be more dependent on awareness (LaBar & Disterhoft, 1998). However, using a false pretense masking task, involving reporting letter cues at a similar volume as CS volume, awareness was found to be critical for acquisition of both delay and trace single-cue eyeblink conditioning (Weidemann, Best, Lee, & Lovibond, 2013). Therefore, while trace conditioning appears to critically depend on awareness, data regarding the role of awareness in delay conditioning appears more equivocal.…”
Section: Declarative Memory and Trace Conditioningmentioning
confidence: 99%
“…Single-cue conditioning produces only very few unaware subjects, whereas more complex conditioning schemes such as differential conditioning (where one stimulus -CS+is associated with the US while the other -CS-is not) prevent more subjects from becoming aware (Carter et al, 2003). The question whether declarative knowledge of the relationship between CS und US is necessary for successful conditioning has sparked a considerable debate amongst scientists Lovibond, Liu, Weidemann, & Mitchell, 2011;Lovibond & Shanks, 2002;Manns et al, 2002;Mitchell, De Houwer, & Lovibond, 2009;Schultz & Helmstetter, 2010;Smith, Clark, Manns, & Squire, 2005;Weidemann, Best, Lee, & Lovibond, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Our data therefore extend evidence from fear conditioning studies actively manipulating contingency awareness, which question the assumption of explicit knowledge about cue-outcome contingencies as a prerequisite in human aversive learning (Knight et al, 2006 ; Schultz and Helmstetter, 2010 ; Raio et al, 2012 ). Unlike approaches actively manipulating contingency awareness to create groups with full vs. no contingency awareness through masking (Knight et al, 2006 , 2009 ; Weidemann et al, 2013 ), explicit instructions and/or distraction (Klucken et al, 2009 ; Schultz and Helmstetter, 2010 ; Tabbert et al, 2011 ) we herein addressed contingency accuracy developed “naturally” over the course of differential learning. While our findings may not generalize to results in individuals fully unaware of CS-US contingencies, varying manifestations of differentially acquired contingency accuracy appear closer to clinical reality in chronic pain patients.…”
Section: Discussionmentioning
confidence: 99%
“…Contingency awareness was accordingly conceptualized as a mediator between associative learning and the display of conditioned responses (Lovibond, 2003 , 2004 ). In support of this notion, several human studies reliably observed conditioned responses in perceived CS valence and in physiological changes of skin conductance responses in aware subjects only, suggesting that contingency awareness is necessary for successful fear conditioning (Lovibond and Shanks, 2002 ; Tabbert et al, 2006 , 2011 ; Klucken et al, 2009 ; Mitchell et al, 2009 ; Lovibond et al, 2011 ; Weidemann and Antees, 2012 ; Weidemann et al, 2013 ). However, others have questioned this assumption given evidence that autonomic fear responses also occur without explicit knowledge regarding contingencies (Wiens and Öhman, 2002 ; Smith et al, 2005 ; Knight et al, 2006 , 2009 ; Schultz and Helmstetter, 2010 ; Raio et al, 2012 ).…”
Section: Introductionmentioning
confidence: 89%